LEVEL OF KNOWLEDGE AND FOOT CARE BEHAVIOR OF PATIENTS WITH DIABETES MELLITUS IN BONEBOLANGO REGENCY - Monoarfa, Hanifa Savanti; Djamaluddin, Nurdiana; Meylandri Arsad, Siti Fatimah (Jambura Nursing Journal, 2025)
Elevated blood glucose (or blood sugar) levels are a sign of a chronic metabolic disease known as diabetes, which over time can cause serious damage to blood vessels, eyes, kidneys, heart, and nerves. Diagnosing people with diabetes as early as possible is very important to prevent or delay complications, avoid premature death, and improve quality of life. If diabetes continues for a long time, it can damage many organs in the body, and these disorders can be life-threatening. The efforts made in preventing complications are by doing foot care. This study aims to determine the level of knowledge and foot care behavior of patients with type 2 diabetes mellitus in the working area of the tapa health center, bone bolango district. This study used a descriptive quantitative method with a cross-sectional approach, data were collected from 106 patients with type 2 diabetes mellitus in the working area of the Tapa Community Health Center, Bone Bolango Regency. The results showed that most respondents had a level of knowledge with a category of less than (44.3%). And had foot care behaviour with a deficient category of (52.8%). Future research is recommended for further researchers to conduct further research on factors related to the behaviour of preventing complications of Type 2 DM.